HIV testing in the maternity ward and the start of breastfeeding: a survival analysis - Glaucia T. Possolli; Márcia L. de Carvalho; Maria Inês C. de Oliveira (Elsevier, 2015)
Objective: The purpose of this study was to analyze the factors that influence of the time between birth and the beginning of breastfeeding, especially at the moment of the rapid HIV test results at hospital admission for delivery. Methods: Cohort study of 932 pregnant women who underwent rapid HIV test admitted in the hospital for delivery in Baby-Friendly Hospitals. The survival curves of time from birth to the first feeding were estimated by the Kaplan-Meier method and the joint effect of independent variables by the Cox model with a hierarchical analysis. As the survival curves were not homogeneous among the five hospitals, hindering the principle of proportionality of risks, the data were divided into two groups according to the median time of onset of breastfeeding at birth in women undergoing rapid HIV testing. Results: Hospitals with median time to breastfeeding onset at birth of up to 60 min were considered as early breastfeeding onset and those with higher medians were considered as late breastfeeding onset at birth. Risk factors common to hospitals considered to be with early and late breastfeeding onset at birth were: cesarean section (RR = 1.75 [95% CI: 1.38-2.22]; RR = 3.83 [95% CI: 3.03-4.85]) and rapid test result after birth (RR = 1.45 [95% CI: 1.12-1.89]; RR = 1.65 [95% CI: 1.35-2.02]), respectively; and hospitals with late onset: starting prenatal care in the third trimester (RR = 1.86 [95% CI: 1.16-2.97]). Conclusions: The onset of breastfeeding is postponed, even in Baby-Friendly Hospitals, when the results of the rapid HIV test requested in the maternity are not available at the time of delivery. Resumo: Objetivo: Identificar os fatores associados ao tempo entre o nascimento e o início da amamentação em mães, especialmente o momento do resultado do teste rápido anti-HIV, na internação para o parto. Metodologia: Estudo de coorte com 932 parturientes que realizaram teste rápido anti-HIV na internação para o parto em Hospitais Amigos da Criança. As curvas de sobrevida do tempo do nascimento até a 1ª mamada foram estimadas pelo método Kaplan-Meier, e o efeito conjunto das variáveis independentes pelo modelo de Cox, com análise hierarquizada. Como as curvas de sobrevida não foram homogêneas entre os 5 hospitais, ferindo o princípio de proporcionalidade de riscos, os dados foram desmembrados em dois grupos segundo o tempo mediano de início de aleitamento materno ao nascer em mulheres submetidas ao teste rápido anti-HIV. Resultados: Hospitais com tempo mediano de até 60 minutos foram considerados como hospitais de início precoce do aleitamento materno e hospitais com tempo mediano superior foram considerados como hospitais de início tardio do aleitamento materno ao nascer. Foram fatores de risco comuns aos hospitais com início precoce e tardio do aleitamento materno ao nascer: parto cesáreo [RR = 1.75 (IC95%:1,38-2,22); RR = 3,83 (IC95%:3,03-4,85)] e resultado do teste rápido após o parto [RR = 1,45 (IC95%:1,12-1,89); RR = 1,65 (IC95%:1,35-2,02)], respectivamente; e nos hospitais com início tardio de aleitamento materno ao nascer: iniciar o pré-natal no 3° trimestre [RR = 1,86 (IC95%:1,16-2,97)]. Conclusões: O início do aleitamento materno vem sendo postergado, mesmo em Hospitais Amigos da Criança, quando os resultados do teste rápido anti-HIV solicitados na maternidade não estão disponíveis no momento do parto. Keywords: Breastfeeding, Hospital birth, AIDS serodiagnosis, Survival analysis, Palavras-chave: Aleitamento materno, Nascimento em hospital, Sorodiagnóstico de AIDS, Análise de sobrevida